THE EFFECTIVENESS OF PICTURE TOWARDS STUDENTS’ WRITING SKILL OF DESCRIPTIVE TEXT - Fitriyeni Fitriyeni; Robbayani Shoghiro (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
The objective of this study is about to see the effectiveness of picture towards students’ writing skill of descriptive text for grade X of SMK Negeri 13 Jakarta in academic year 2018/2019. This research is quantitative using quasi-experimental method. The population was grade X students of SMK Negeri 13 Jakarta. It was conducted in two classes as sample. The instruments used were documentation and test. T-test was used to determine whether there was a significance difference or not between students’ scores in experimental class and students’ scores in control class. The result of the study showed that the calculation of the value of ttest is 2.92 and the degree of freedom (df) is 54. The value of t-table in the degree of freedom and at the degree of significance 5% is 1.674. It means picture is effective towards students’ writing skill of descriptive text for grade X at SMK Negeri 13 Jakarta in academic year 2018/2019. Finally the writer suggests that teachers should use picture as one of the media in teaching writing of descriptive text.